Career management in government - Dey, Bata K. (1997)
With a discussion on conceptual issues, including definition, objectives and needs of career management, the author focusses on a detailed critical examination of Indian scenario on career management that prevails even after an elapse of 50 years, despite injecting of radical value changes in personnel system following enforcement of New Economic Policy and endorsement of there by the Fifth Pay Commission. In the concluding part, he draws special attention to the pathetic lack of consciousness and total neglect on the part of the Central nodal agency to the needs of Career Management as even the Fifth Pay Commission did nothing more than making a perfunctory reference to it. - Reproduced
Keywords: Civil service - India; Civil service